Permacol collagen paste for cryptoglandular and Crohn's anal fistula - Brunner, Michaela; Schneider, Ignaz Hans Friedrich; Guenther, K.; Grützmann, Robert; Matzel, Klaus (Techniques in Coloproctology, 2019)
BackgroundPermacol collagen paste, an acellular crosslinked porcine dermal collagen matrix suspension, is a new treatment option for anal fistula. Data remain limited, however, and as yet only the results of one case of Crohn's fistula treated with Permacol paste has been reported. The aim of this study was to assess the use of Permacol collagen paste in patients with cryptoglandular and Crohn's perianal fistulae.MethodsA prospective study was conducted on patients with anal fistula, treated with Permacol paste. Patients were followed at 1week, 6 and 12months, and on demand thereafter. The main focus was on fistula healing and postoperative continence. The former was defined as the absence of signs of recurrence on clinical examination, proctoscopy and rigid rectoscopy. Fecal incontinence was assessed before surgery and at each follow-up.ResultsThirty patients (19 women, 11 men; mean age 46years), 12 (40%) of whom had Crohn's disease were included. The average number of previous fistula operations was 6. All patients had 6months of follow-up, and 24 patients (80%) had 12months of follow-up. The healing rate in all patients was 57% (17 of 30 patients) at 6months and 63% (15 of 24 patients) at 12months. One patient reported a worsening of fecal incontinence at 12 months; 2 patients had adverse events (perianal pain: n=1, fluid accumulation n=1) requiring fistula drainage. Patient characteristics, healing, incontinence, and adverse events did not differ significantly between patients with and without Crohn's disease.ConclusionsOur data indicate that Permacol paste is a safe and moderately effective treatment for cryptoglandular and Crohn's fistulae.
CRIS-Team WoS Importer:2019-04-12